Prioritizing Strategies to Enhance Teachers’ Technological Self-Efficacy: A Nominal Group Technique approach - Subramaniam, Sutha; Ismail, Aziah; Ahmad, Nur Suhaila (Environment-Behaviour Proceedings Journal, 2025)
This study explores the enhancement of teachers’ technology integration self-efficacy (TTISE) through the Nominal Group Technique (NGT), which involved seven educational experts. Recognizing the pivotal role of self-efficacy in effective educational technology integration, the study aims to develop strategies for improving self-efficacy among teachers. Findings indicate that mastery and vicarious experiences are critical in fostering self-efficacy. Conclusively, strategies such as incremental challenges and peer observation have proven effective in sustaining technology integration. Thus, further research should investigate the impact of social persuasion and emotional states on TTISE and address barriers to the full utilization of mastery and vicarious experiences.